2009
DOI: 10.1021/tx900265z
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Quantitative Proteomic Approach To Identifying Sulfur Mustard-Induced Protein Phosphorylation Cascades

Abstract: Sulfur mustard [SM, bis-(2-chloroethyl) sulfide] is a potent alkylating agent and chemical weapon. While there are no effective treatments for SM-induced injury, current research focuses on understanding the molecular changes upon SM exposure. Indeed, efforts that seek a more comprehensive analysis of proteins and post-translational modifications are critical for understanding SM-induced toxicity on a more global scale. Furthermore, these studies can uncover proteins previously uncharacterized in SM-exposed ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In 2010, Everley et al showed that guanine nucleotide exchange factors (GEFs) and GTPase‐activating proteins (GAPs) were down‐regulated by up to two folds in an in vitro study on human keratinocytes model after SM‐exposure. However phosphorylated proteins showed up to threefold increases in the SM‐exposed cells …”
Section: Proteomics Assessment Of Sulfur Mustard Exposed Victimsmentioning
confidence: 99%
“…In 2010, Everley et al showed that guanine nucleotide exchange factors (GEFs) and GTPase‐activating proteins (GAPs) were down‐regulated by up to two folds in an in vitro study on human keratinocytes model after SM‐exposure. However phosphorylated proteins showed up to threefold increases in the SM‐exposed cells …”
Section: Proteomics Assessment Of Sulfur Mustard Exposed Victimsmentioning
confidence: 99%
“…Both cell types were used in several studies before and were found very well suited for the investigation of TRPA1-related effects [ 23 , 40 , 41 ]. Several genes and proteins have been reported to be specifically up-regulated in mouse skin and in human keratinocytes after exposure to SM [ 42 , 43 ]. Thus, we focused on proteome changes after SM exposure with special focus on the involvement of TRPA1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, comprehensive analyses of proteins and posttranslational protein modifications have contributed to unveil the complex pathophysiology of SM and have given new impulses for the development of new potential therapeutic measurements [14][15][16].…”
Section: Introductionmentioning
confidence: 99%